Investigation of the Relationship between Organizational Citizenship Behavior and Human Resources Productivity: Based on the Staff Viewpoints in the Selected Hospitals of Yazd City, 2018 - Roohollah Askari; Zahra Sadat Seyed Rezaei; Somayeh Mahdiyan; Masoomeh Pishehvaran (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Organizations usually seek for decreasing problems such as slacking and aggression and increase the behaviors that lead to a benefit such as productivity for the organization. One of the factors creating productivity in the organization is organizational citizenship behavior. Therefore, this research is aimed at investigating the relationship between organizational citizenship behavior and human resources productivity in the selected hospitals of ShahidSadoughi University of Medical Sciences in Yazd, 2018. Methods: This research is a descriptive correlation study. The population includes the staff of three selected hospitals in Yazd. Out of the mentioned population, 211 people were selected by random sampling. Data collection tool was a standard questionnaire. Reliability and validity of the tool have been already approved in a similar study. The questionnaire consists of two parts including: organizational citizenship behavior, , and human resources productivity. Data analysis was done by Pearson correlation, regression, t-test, and analysis of variance in SPSS16. Results: The mean total scores of organizational citizenship behavior and human resources productivity were 3.06 ± 0.32 and 3.50 ± 0.62, respectively. The investigation of the mean scores of organizational citizenship behavior in each aspect indicated that the highest mean score, 4.11 ± 0.54, belonged to altruism and the lowest, 1.58 ± 0.75, belonged to sportsmanship. Among the various aspects of human resources productivity, the highest mean score was for competency, 3.89 ± 0.55, and the lowest was obtained for support, 3.22 ± 0.57. Based on the employees' perspectives, there was a positive and significant relationship between OCB and human resources productivity (P-value < 0.001 and r = 0.297). Conclusion: OCBhas a direct effect on resources productivity based on the staff viewpoints in educational hospitals. So, providing the opportunity of promotion of organizational citizenship behaviors can be an effective factor in increasing human resources productivity.